Estudo da época de semeadura de genótipos promissores de cevada - Zocche, Jean Carlos (2019)
To evaluate the influence of sowing season on the agronomic characteristics of promising and commercial breeding barley genotypes in two agricultural crops in the city of Guarapuava, PR. The experimental design was a randomized block design with three replications, in a factorial scheme (12x2x2), 12 genotypes evaluated, with potential for malting production in two sowing seasons and two agricultural crops. Among the genotypes evaluated, these were divided into two groups, one composed of 6 promising genotypes from the breeding program, which involves, besides FAPA, Embrapa PFC and Ambev (GP1, GP2, GP3, GP4, GP5 and GP6) and six commercial barley genotypes (BRS 195, BRS BRAU, ANAG 01, ANA 02, Danielle, Irina), both with characteristics for malt production and the sowing times evaluated were: season 1 (30/06) and season 2 (16/07). The experiment was developed during the agricultural crops of 2017 (Safra 1) and 2018 (Safra 2) in the experimental area of the Agrarian Agricultural Research Foundation - FAPA, Entre Rios, in the municipality of Guarapuava, PR, under no-tillage system. The following agronomic characteristics were evaluated: number of tillers (NP); number of grains per ear (NGE) and grain yield (PROD), these in each experimental plot and in both sowing times and agricultural crops. Subsequently, the means were submitted to individual and joint analysis of variance and grouped by the Scott-Knott test, at 5% probability. The agronomic characteristics of the number of grains per spike and grain yield were influenced by the sowing season, the crop season and the brewing barley genotypes evaluated, being the season 1 (June 30) with better results. The NP was positively influenced by the crop season being higher in Harvest 2 (2018), which is dependent on the promising commercial genotype evaluated. The promising genotypes GP1 and GP6 were distinguished by obtaining grain yield similar to the commercial cultivars ANA 02 and Irina, at the sowing times and agricultural crops evaluated.